No Longer the Elephant Outside the Room: Why the Ukraine Crisis Reflects a Deeper Shift Towards German Leadership of European Foreign Policy. Issue 4 (2nd October 2018) - Wright, Nicholas
Abstract : Germany's position as Europe's predominant economic power has long been recognised. In recent years it has also emerged as a leading European foreign policy actor, although its willingness and capacity to play an explicit leadership role are debated. In particular, the 'geo-economic' analyses of Kundnani ( The Paradox of German Power, 2014) and Szabo ( Germany, Russia and the Rise of Geo-Economics, 2015) argue that German foreign policy is increasingly focused on narrow calculations of national interest resulting in a decline in the instinctive multilateralism that has characterised its international engagement since 1949. This article uses the German response to the current Ukraine crisis to contest these arguments. Examining both German engagement with the EU's Common Foreign and Security Policy, a crucial component of its foreign policy-making, and its response to the Ukraine crisis, the article contends that far from becoming more unilateral, a more vigorous German multilateralism is emerging. This seeks to fully utilise all available multilateral channels and in turn reflects how far the centre of gravity in European foreign policy-making has shifted towards Berlin.